Pengaruh Kecukupan Modal dan Kompetisi Terhadap Profitabilitas Bank Syariah di Indonesia - Mauliza, Dessy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
ABSTRACTÂ This study is conducted to analyze the influence of capitalÂ adequacyand competition against sharia banksâ profitability. This study applied census method , where studyâs population was all sharia bank enlisted in Bank of Indonesia within 2013 until 2015 period. Data used in this study were secondary data.Results of this study show that capitalÂ adequacyand competition together influenced sharia banksâ profitability. Partially, capitalÂ adequacyhad negative influence against banksâ profitability while competition had positive influence against sharia banksâ profitability.Key words: Capital Adequacy Ratio, Competition, Profitability (ROA)